Methods of group exercise instruction - Yoke, Mary M. 1953-; Kennedy, Carol A. 1958- (Human Kinetics, 2020)
In the constantly evolving world of fitness and exercise, it is challenging to become--and remain--an effective group exercise instructor. Methods of Group Exercise Instruction, Fourth Edition With Online Video, offers expert guidance in a variety of group exercise formats so current and aspiring instructors can hone their skills and create demand for their services. The authors--who have dozens of years of experience--thoroughly explain group exercise training principles, correction and progression techniques, and safety tips. They also have taught this course within a university setting. This research-based text will enhance the skills of group exercise leaders and prepare them to lead more dynamic, safe, and effective classes for clients of differing ages, abilities, and interests